The Role of Social Engineering in Shaping Laws for Effective Rehabilitation of Drug Addicts in Indonesia: A Case Study of Community-Based Intervention - Ngaisah, Siti; Widoyoko, Wredha Danang; Rahmawati, Diah Ayu; Haryono, Haryono; Kurniawan, Bagus Ananda (Westscience Press, 2024)
This study examines the role of social engineering in shaping legal frameworks to enhance the rehabilitation of drug addicts in Indonesia, focusing on community-based interventions. Using a juridical analysis of legislation and case studies, the research identifies gaps in the current legal framework, including its punitive focus, insufficient support for rehabilitation programs, and lack of community involvement. The findings underscore the potential of social engineering principles to address these shortcomings by designing laws that prioritize rehabilitation, promote community participation, and reduce stigma. Drawing from international best practices, the study provides actionable recommendations to reform Indonesia's narcotics laws, fostering a balanced approach that integrates rehabilitative justice with community-driven solutions. This research contributes to the discourse on drug policy reform, advocating for a more compassionate and effective system that aligns with global standards.